Given:
sin A + cos A = m -- equation (1)
sec A + Cosec A = n -- equation (2).
Find:
value of n(m+1)(m-1)
Solution:
We have to find:
n(m + 1)(m - 1)
using (a + b)(a - b) = a² - b² we get,
⟹ n (m² - 1²)
⟹ m²n - n
Putting the values from equations (1) & (2) we get,
⟹ (sin A + cos A)² * (sec A + Cosec A) -
(sec A + Cosec A)
(a + b)² = a² + b² + 2ab
⟹ (sin² A + cos² A + 2sin A Cos A ) * (sec A + Cosec A) - sec A - Cosec A
using the identity sin² A + cos² A = 1 we get,
⟹ ( 1 + 2 sin A cos A ) * (sec A + Cosec A) - sec A - Cosec A
⟹ 1(sec A + Cosec A) + 2sin A cos A(sec A + Cosec A) - sec A - Cosec A
⟹ sec A + Cosec A + 2 sin A * cos A * sec A + 2 sin A cos A Cosec A - sec A - Cosec A
using sin A * Cosec A = 1 & cos A * sec A = 1 we get,
( sec A + Cosec A & - sec A - Cosec A are being cancelled )
⟹ 2 sin A + 2 cos A
⟹ 2 (sin A + cos A)
Putting the value sin A + cos A from equation (1) we get,
⟹ 2m
∴ n (m + 1)(m - 1) = 2m.
I hope it will help you.
Regards.